Bahan Ajar Elektronik Berbantuan Geogebra Pada Materi Statistika Siswa SMK - Rarri Ryandi; Diah Dwi (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
This study aims to utilize GeoGebra electronic teaching materials to create a learning path in understanding statistical material. Design Research is used as a research method that can formulate and describe theories in statistical learning. The learning was designed at an early stage and tested on 24 students of XI Grade at SMK Baiturrahim. The results obtained in this study are a learning trajectory consisting of 3 activities, activity 1; data presentation, activity 2; data centering, and activity 3; statistical questions. From the resulting activities, it can be concluded that learning with GeoGebra-assisted electronic teaching materials can increase students' learning motivation and increase students' interest in learning mathematics, especially statistical material.